Perch Hydrolysates from Upcycling of Perch Side Streams Accelerate Wound Healing by Enhancing Fibroblasts to Secrete Procollagen I, Fibronectin, and Hyaluronan - Jia-Feng Chang; Chih-Yu Hsieh; Ling-Ni Chen; Mao-Hsiang Lee; Yi-Han Ting; Chi-Yu Yang; Chih-Cheng Lin (Current Issues in Molecular Biology)
Wound healing incurs various challenges, making it an important topic in medicine. Short-chain peptides from fish protein hydrolysates possess wound healing properties that may represent a solution. In this study, perch hydrolysates were produced from perch side steams using a designed commercial complex enzyme via a proprietary pressure extraction technique. The average molecular weight of the perch peptides was 1289 kDa, and 62.60% of the peptides had a low molecular weight (≤1 kDa). Similarly to the beneficial amino acid sequence FPSIVGRP, FPSLVRGP accounted for 6.21% abundance may have a potential antihypertensive effect. The concentrations of collagen composition and branched-chain amino acids were 1183 and 1122 mg/100 g, respectively. In a fibroblast model, active perch peptides accelerated wound healing mainly by increasing the secretion of procollagen I, fibronectin, and hyaluronan. In an SD rat model established to mimic human wounds, orally administered perch hydrolysates with a molecular weight below 2.3 kDa accelerated wound healing, which mainly resulted from collagen-forming amino acids, branched-chain amino acids, and matrikine. Collectively, the residue of perch extract can be upcycled via a hydrolysis technique to produce not only bioactive sequences but also short-chain peptides. Considering the therapeutic potential to promote wound healing, such by-products are of great value and may be developed as dietary nutraceuticals.